Interns' Perceived Level of Proficiency After General Surgery Rotation: A Cross-Sectional Study From Saudi Arabia - Elhilu, Abdelkhalig; Ghazwani, Salman; Adawi, Essa A; Abdelwahab, Siddig I (Curēus (Palo Alto, CA), 2024)
The role of interns during general surgical rotation is crucial in shaping their future careers as surgeons. Surgical rotation offers a unique opportunity to gain valuable hands-on experience in fast-paced and challenging environments. However, interns often face significant challenges in obtaining the necessary practical training to develop proficiency in surgical techniques. This article aims to analyze some aspects of the accumulated competency of interns during their general surgery rotation, focusing on the range of skills and knowledge gained, in addition to the challenges faced. We conducted a cross-sectional study using an anonymous web-based self-assessment questionnaire. The target population of the study included all Jazan University medical interns enrolled in the academic year 2022-2023. Most participants showed low-to-average levels of proficiency in monitoring clinical evolution and treatment plans, ranging from fundamental awareness (n = 17, 17.5%) to working knowledge (n = 51, 52.6%), with only three participants (3.1%) reporting an expert level of proficiency. The same pattern was observed in the documentation of patient records (range: 7.2%, n = 7 for fundamental awareness to 42.3%, n = 41 for working knowledge). However, a significant proportion saw themselves as either proficient (n = 23, 23.7%) or experts (n = 15, 15.5%) in this aspect. Regarding bedside procedures, such as venipuncture, proctoscopy, nasogastric tube insertion, and urethral catheterization, the participants showed different proficiency levels, with the lowest in proctoscopy, where 66 (68.0%) of the participants reported only fundamental awareness. The results also revealed low perceived proficiency in performing surgical skin incisions, wound suturing, knot tying, application of surgical skin clips, and abscess drainage, with the lowest proficiency observed in the excision of superficial lumps as more than half of the participants reported only fundamental awareness (n = 51, 52.6%). The results of this study indicate that documentation and monitoring of patient progress are the competencies mastered most by the majority of interns during their rotations in general surgery. However, the interns' overall level of proficiency in bedside procedures and basic surgical skills acquired during their rotation was low to average. Additionally, interns were dissatisfied with their training and the opportunities provided for them to actively engage in performing procedures in the operating room. This low proficiency is unrelated to pre-internship academic achievement, sex, or interest in future surgical careers. This suggests that efforts are needed to develop strategies to enhance interns' satisfaction and engagement, ultimately improving their overall experience during internships.